PREFERENSI GENERASI X DAN Y DALAM MENGGUNAKAN MEDIA ONLINE DAN MEDIA TELEVISI - Wulandari, Dwi Rohma; Yusaputra, Muhammad Isa; Haidar, Nur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
This research uses quantitative research methods, the data collection technique is a questionnaire from Generation X in Mantikulore District, Palu City. Data collection techniques accompanied by lists of questions to respondents. The number of samples used in this research was 99 respondents. The data analysis technique used to measure the use of online media and television media is by calculating all questionnaire items from each study. The test results show that both media have shows that are often used by generation X, but television media (X2) is higher than online media (X1) in generation This is shown by the results of calculating the highest percentage value for television media from the question, 89% and online media with a percentage of 87%. So the conclusion is Ho: The preference for watching online media shows is lower than the preference for watching television media shows.